Age Influences the Prognosis of Anaplastic Thyroid Cancer Patients - Kong, Na; Xu, Qiqi; Zhang, Ziqin; Cui, Aimin; Tan, Shen; Bai, Nan (Frontiers in Endocrinology, 2021)
Background The staging system for patients with anaplastic thyroid cancer (ATC) was updated in the 8th edition of the American Joint Committee on Cancer Staging Manual. A cut-off age of 55 years was stipulated as a prognostic factor for differentiated thyroid cancer; however, age was not considered for ATC patients. To this end, this study investigated the relationship between age at diagnosis and prognosis of ATC patients. Methods The clinical information on ATC patients was acquired from the Surveillance, Epidemiology, and End Results Program public database. Youden’s index and X-tile analyses were used to calculate the high-point age at diagnosis associated with prognosis. Cox proportional hazards models, Kaplan-Meier curves, and 1000-person-year were then used for verifying the accuracy of the high-point age. Results After inclusion/exclusion criteria was applied, 586 patients were included in this study. The high-point age was determined to be 70 years by both the Youden’s index and X-tile plot methods. The hazard ratio was 1.662 (95% confidence interval [CI]: 1.321-2.092), indicating that there was an increased risk of poor prognosis for patients > 70 years of age. The cancer-specific mortality rates per 1000-person-years for patients ≤ and > 70 years-old were 949.980 (95% CI: 827.323-1090.822) and 1546.667 (95% CI: 1333.114-1794.428), respectively. P-values were < 0.001 for the results shown above. Conclusion Our study found that age influenced the prognosis of ATC patients. Furthermore, we determined that the high-point age at diagnosis was 70 years and that > 70 years of age was associated with a poor prognosis. These results provide a useful addition to the staging manual and can improve the diagnosis, treatment strategies and prognosis of ATC patients.